2016
DOI: 10.1038/tp.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute aerobic exercise on neural correlates of attention and inhibition in adolescents with bipolar disorder

Abstract: Executive dysfunction is common during and between mood episodes in bipolar disorder (BD), causing social and functional impairment. This study investigated the effect of acute exercise on adolescents with BD and healthy control subjects (HC) to test for positive or negative consequences on neural response during an executive task. Fifty adolescents (mean age 16.54±1.47 years, 56% female, 30 with BD) completed an attention and response inhibition task before and after 20 min of recumbent cycling at ~70% of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…The therapeutic and preventive potential of physical exercise for PBD, for example, is an almost entirely untouched topic. 260,261 …”
Section: | Conclusionmentioning
confidence: 99%
“…The therapeutic and preventive potential of physical exercise for PBD, for example, is an almost entirely untouched topic. 260,261 …”
Section: | Conclusionmentioning
confidence: 99%
“…In the domains of incomplete outcome data and selective reporting, all studies were judged as having a low risk of bias. Furthermore, with regard to the domain of "other bias", the majority of studies were judged as having an unclear bias because the study design did not meet recent recommendations [33] (e.g., it used only a posttest comparison [38,39,71,73,[99][100][101][102][103][104] and/or the prescription of exercise intensity was not optimal because it was not based on a graded exercise test [39,[71][72][73][103][104][105]).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…In the reviewed studies, the acute effects of physical exercise were studied in healthy children [71,73], adolescents with and without bipolar disorder [105], younger adults with attention deficit hyperactivity disorder (ADHD) [100,102], healthy younger adults [38,39,72,99,101,102,106], and healthy older adults [103,104,107]. A detailed overview of the sample characteristics (e.g., age, gender, BMI, and cardiorespiratory fitness level) can be found in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study examining the effects of acute exercise on adolescents completing a measure of executive functioning (go/no-go task) has shown that acute aerobic exercise is able to influence deficits in deactivating attention and activating inhibition 27. This line of inquiry is important to understand the potential therapeutic efficacy of exercise for bipolar disorder.…”
Section: Neurobiological Effects Of Exercisementioning
confidence: 99%